Hip fracture treatment in Norway: deviation from evidence-based treatment guidelines: data from the Norwegian Hip Fracture Register, 2014 to 2018 - Kjærvik, Cato (Bone Jt Open, 2020)
AIMS: The aim of this study was to describe variation in hip fracture treatment in Norway expressed as adherence to international and national evidence-based treatment guidelines, to study factors influencing deviation from guidelines, and to analyze consequences of non-adherence. METHODS: International and national guidelines were identified and treatment recommendations extracted. All 43 hospitals routinely treating hip fractures in Norway were characterized. From the Norwegian Hip Fracture Register (NHFR), hip fracture patients aged > 65 years and operated in the period January 2014 to December 2018 for fractures with conclusive treatment guidelines were included (n = 29,613: femoral neck fractures (n = 21,325), stable trochanteric fractures (n = 5,546), inter- and subtrochanteric fractures (n = 2,742)). Adherence to treatment recommendations and a composite indicator of best practice were analyzed. Patient survival and reoperations were evaluated for each recommendation. RESULTS: Median age of the patients was 84 (IQR 77 to 89) years and 69% (20,427/29,613) were women. Overall, 79% (23,390/29,613) were treated within 48 hours, and 80% (23,635/29,613) by a surgeon with more than three years’ experience. Adherence to guidelines varied substantially but was markedly better in 2018 than in 2014. Having a dedicated hip fracture unit (OR 1.06, 95%CI 1.01 to 1.11) and a hospital hip fracture programme (OR 1.16, 95% CI 1.06 to 1.27) increased the probability of treatment according to best practice. Surgery after 48 hours increased one-year mortality significantly (OR 1.13, 95% CI 1.05 to 1.22; p = 0.001). Alternative treatment to arthroplasty for displaced femoral neck fractures (FNFs) increased mortality after 30 days (OR 1.29, 95% CI 1.03 to 1.62)) and one year (OR 1.45, 95% CI 1.22 to 1.72), and also increased the number of reoperations (OR 4.61, 95% CI 3.73 to 5.71). An uncemented stem increased the risk of reoperation significantly (OR 1.23, 95% CI 1.02 to 1.48; p = 0.030). CONCLUSION: Our study demonstrates a substantial variation between hospitals in adherence to evidence-based guidelines for treatment of hip fractures in Norway. Non-adherence can be ascribed to in-hospital factors. Poor adherence has significant negative consequences for patients in the form of increased mortality rates at 30 and 365 days post-treatment and in reoperation rates. Cite this article: Bone Joint Open 2020;1-10:644–653.